Population studies of Brevicoryne brassicae (L.), its parasites and hyperparasites in England - Tock, Hing Chua (John Wiley & Sons, Inc, 1977)
Brevicoryne brassicae (L.) is a cosmopolitan aphid, feeding mainly on Crucifers (BONNEMAISON, 1965). It normally overwinters as eggs, but small colonies may survive mild. winters (PETHERBRIDGE and WRIGHT, 1938). In the spring, freshly planted Cruciferous crops are colonized by fundatrices or immigrant alates. Throughout spring, summer and autumn, B. brassicae reproduces parthenogenetically. Later in the year, however, owing to low temperatures and shorter photoperiods, sexual forms begin to appear and overwintering eggs are laid on the Cruciferous hosts. In the Netherlands, HAFEZ (1961) has shown that the number of generations per year to be between 6 and 11.